Individual and corporate social responsibility - Roland Bénabou; Jean Tirole (Institute for the Study of Labor (IZA), 2009)
Society's demands for individual and corporate social responsibility as an alternative response to market and distributive failures are becoming increasingly prominent. We first draw on recent developments in the psychology and economics of prosocial behavior to shed light on this trend, which reflects a complex interplay of genuine altruism, social or self image concerns, and material incentives. We then link individual concerns to corporate social responsibility, contrasting three possible understandings of the term: the adoption of a more long-term perspective by firms, the delegated exercise of prosocial behavior on behalf of stakeholders, and insider-initiated corporate philanthropy. For both individuals and firms we discuss the benefits, costs and limits of socially responsible behavior as a means to further societal goals.
Keywords: D64; D78; H41; L31; 330; Corporate social responsibility; socially responsible investment; image concerns; shareholder value; Soziales Verhalten; Altruismus; Corporate social responsibility; Firmenimage; Shareholder Value; Verhaltensökonomik